(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
In Verbal Behavior, Skinner defined verbal behavior as behavior that modifies the environment by other people’s action. From the analysis of speaker’s interaction with the environment and the listener, he classified the elementary verbal relations - mand, tact, intraverbal, textual, echoic and transcriptive - on witch the second order verbal processes act - the autoclitic process. The article is a didactic one and it has the objective of defining and serving of instruction in order to make a functional classification of those relations, by illustrating the classification of descriptive, qualifying, quantifying, manipulative, relational, and of composition autoclitics unities from empirical data got from record of conversation among students about the polemic topic “adoption of children by homosexual couples”.